2013
DOI: 10.1186/1745-6215-14-254
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture for chemotherapy-induced peripheral neuropathy: study protocol for a pilot multicentre randomized, patient-assessor-blinded, controlled trial

Abstract: BackgroundChemotherapy-induced peripheral neuropathy (CIPN) is the main dose-limiting side effect of neurotoxic chemotherapeutic agents. CIPN can lead not only to loss of physical function, difficulties in activities of daily living (ADLs), and decreased quality of life, but also to dose reduction, delay or even cessation of treatment. Currently, there are few proven effective treatments for CIPN. This randomized controlled clinical trial is designed to evaluate the effects and safety of electroacupuncture (EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Acupuncture may also be effective, but a current lack of RCTs with positive results exists for this endpoint. An ongoing pilot study by Kim et al [78] will be the first multicenter randomized patient-assessor–blinded trial to evaluate electroacupuncture versus sham acupuncture for CIPN using EORTC-QLQCIPN20.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture may also be effective, but a current lack of RCTs with positive results exists for this endpoint. An ongoing pilot study by Kim et al [78] will be the first multicenter randomized patient-assessor–blinded trial to evaluate electroacupuncture versus sham acupuncture for CIPN using EORTC-QLQCIPN20.…”
Section: Discussionmentioning
confidence: 99%
“…The deactivated EA apparatus was designed to show a same flashing light with the real EA apparatus, but no output of electric current. Though often used in clinical trials [ 39 , 40 ], this deactivated EA control method has not yet been tested. An assessment of the effectiveness of blinding, by asking the patients which group they thought they were assigned to, was not done in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as research continues into the role of pharmacological agents for treatment and/or prevention of oxaliplatin-induced peripheral neuropathy; interest in nonpharmacological treatment options is increasing. Studies have been lacking on non-pharmacological therapy for the treatment of oxaliplatin-peripheral neuropathy, although some clinical studies have been performed on acupuncture for the treatment of chemotherapy-induced peripheral neuropathy [39][40][41][42]. These studies reported improvements following acupuncture in the Visual Analog System (VAS) pain scale, gait, and nerve conduction tests, and reduced use of pain medication.…”
Section: Discussionmentioning
confidence: 99%